Association between SCN5A R225Q variant and dilated cardiomyopathy: potential role of intracellular pH and WNT/β-catenin pathway. Issue 12 (14th June 2022) - Hu, Jingjing; Yang, Kun; Zhao, Yongchao; Wei, Zilun; Yang, Lebing; Gao, Rifeng; Wu, Yonghui; Xu, Lei; Xu, Sujuan; Hu, Kai; Sun, Aijun; Ge, Junbo
Abstract : Background: The SCN5A variant is a common cause of familial dilated cardiomyopathy (DCM). We previously reported a SCN5A variant (c.674G>A), located in the high-risk S4 segment of domain I (DI-S4) region in patients with idiopathic DCM and R225Q knockin (p.R225Q) mice carrying the c.674G>A variant exhibited prolonged baseline PR intervals without DCM phenotypes. In this study, we explored the association and mechanism between R225Q variant and DCM phenotype. Methods: Prevalence of DI-S4 variant was compared between patients with idiopathic DCM and the control participants. R225Q knockin and wild-type (WT) mice were subjected to doxorubicin (DOX), D-galactose (D-gal) or D-gal combined with DOX. Results: Clinical data suggested that the prevalence of DI-S4 variant was higher in DCM group than in the control group (4/90 (4.4%) vs 3/1339 (0.2%), p<0.001). Cardiomyocytes from R225Q knockin mice treated with D-gal and DOX exhibited more significant hypertrophic phenotype and weaker contraction/dilation function and an increased level of apoptosis as compared with WT mice. Mechanistically, we found that R225Q variant could increase intracellular pH and further induce the activation of the WNT/β-catenin pathway as well as the overexpression of pro-hypertrophic and pro-apoptotic targets. WNT-C59 inhibitor improved cardiac function in the R225Q knockin mice treated with D-gal and DOX. Conclusion: Our results suggest that R225Q variant is associated with increased susceptibility to DCM. Ageing could enhance this process via activating WNT/β-catenin signaling in response to increased intracellular pH. Antagonising the WNT/β-catenin pathway might be a potential therapeutic strategy for mitigating R225Q variant-related DCM pathogenesis.